2019
DOI: 10.1371/journal.pone.0218537
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of AKT kinase increase LDL receptor mRNA expression by two different mechanisms

Abstract: Protein kinase B (AKT) is a serine/threonine kinase that functions as an important downstream effector of phosphoinositide 3-kinase. We have recently shown that MK-2206 and triciribine, two highly selective AKT inhibitors increase the level of low density lipoprotein receptor (LDLR) mRNA which leads to increased amount of cell-surface LDLRs. However, whereas MK-2206 induces transcription of the LDLR gene, triciribine stabilizes LDLR mRNA, raising the possibility th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… 49 The reduction in active SREBP-2 results in a decrease in LDLR protein level, owing to the reduced binding of SREBP-2 to the cognate sterol regulatory element-1 (SRE-1) in the LDLR promoter. 50 These findings suggested that LDLR might act downstream of the HIF-1α pathway. Furthermore, silencing of HIF-1α was found to increase LDLR levels in HepG2 cells stimulated with oleic acid and palmitic acid.…”
Section: Discussionmentioning
confidence: 96%
“… 49 The reduction in active SREBP-2 results in a decrease in LDLR protein level, owing to the reduced binding of SREBP-2 to the cognate sterol regulatory element-1 (SRE-1) in the LDLR promoter. 50 These findings suggested that LDLR might act downstream of the HIF-1α pathway. Furthermore, silencing of HIF-1α was found to increase LDLR levels in HepG2 cells stimulated with oleic acid and palmitic acid.…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that LDLR and CD36 gene expressions were markedly upregulated by olanzapine treatment, suggesting that olanzapine can regulate LDLR and CD36 at the transcriptional level, independently of its post‐translational effects via the PCSK9 pathway. Inhibitors of protein kinase B (Akt) increase LDLR expression through extracellular signal‐regulated kinase (ERK)‐dependent stabilization of LDLR mRNA, 34,35 and proliferative and neuroprotective effects of olanzapine in vitro appear to be mediated by activation of PI3K/Akt and ERK pathways in PC12 cells 36 . In addition, it has been reported that the hepatic mTOR signaling pathway is enhanced in olanzapine‐induced dyslipidemia 37 and plays a crucial role in regulating lipid biosynthesis and lipogenesis via peroxisome proliferator‐activated receptor gamma (PPARγ), 38 a key regulator of CD36 38–40 .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that two pharmacologic inhibitors of the protein kinase AKT, MK-2206 and triciribine, increase LDLR mRNA levels by two different mechanisms ( 32 , 38 , 39 ). MK-2206 stimulates LDLR expression by inducing the proteolytic activation of SREBP2, while triciribine enhances LDLR mRNA stability.…”
Section: Discussionmentioning
confidence: 99%